Antifibrotic Effect of Transforming Growth Factor Beta 1 Inhibitor Extract from Streptomyces SP.Strain H6552 on Human Hepatic Stellate Cells - Lim, Chooi Ling (2010)
Liver fibrosis is a result of the body’s natural wound healing response, but excessive scarring leads to significant morbidity and mortality. Transforming growth factor-beta 1 (TGF-β1) inhibitors that hinder the fibrotic mechanism are currently being developed. However, an effective anti-fibrotic drug remains elusive and in vitro anti-fibrotic studies using hepatic stellate cells (HSCs) are often complicated by the dynamic plasticity of these cells which become spontaneously activated in culture. In this study, we aimed to assess the quiescing effect of seeding LX-2 human HSC line on Matrigel-coated culture plates, and evaluate the anti-fibrotic activity of soil-derived Streptomyces (S.) sp. H6552 extract and/or active fraction and SB431542 (a commercial TGF-β receptor inhibitor) on LX-2 cells. In HSC culture studies, LX-2 cells were seeded either on non-coated or Matrigel-coated culture plates and subjected to fibrotic marker analyses, Oil Red O staining, and phase contrast microscopy. In the next chapter, S.sp. H6552 was cultured in mannitol-peptone medium and its metabolites were isolated via a ‘shake-flask’ method followed by acetone extraction, HPLC analysis and fractionation of crude H6552 extract. A bioassay-guided screening selection yielded the potential bioactive fraction (F3). Viability tests (MTT assay) were performed to evaluate the cytotoxicity of the crude extract. LX-2 cells were then treated with either the extract, F3 or SB431542 with or without 8 to 10 ng/mL TGF- β1 induction, followed by assays for anti- fibrotic activity. Proliferation of cells were assessed via ³H-thymidineincorporation, mitochondrial stress was evaluated by Mito Tracker Red®fluorescence staining, and cytoplasmic lipid accumulation analyses for quiescence determination was performed via Oil Red O staining. TGF-β1 inhibitory activity was evaluated by Smad reporter and IgA promoter luciferase assays, while expression of fibrotic markers were analysed via Real-Time PCR, immunoblotting, and immunocytochemistry. Aprogressively activated morphology was observed in LX-2 cells with prolonged culture on plastic, but this phenomenon was inhited on Matrigel attachment substrate whereby an adipocytic, quiescent phenotype was conserved with concurrent reduction in TGF-β1-induced alpha-smooth muscle actin (α-sma) protein expression. S. sp. H6552 extra was found to be non-cytotoxic but exerted strong anti-profilerative activity from 1 mg/mL compared to untreared control (p<0.01), while the influence of F3 on profileration was insignificant. Mitochondrial staining showed a possible antioxidative effect of 2 mg/mL H6552 crude extract on LX-2 cells, while 100µg/mL F3 induced a quiescent, adipocytic phenotype in 73.85 ± 2.05% of treated cells (p<0.05). Smad3 reporter activity was inhibited by 50% after 2 mg/mL crude extract treatment to TGF-β1-induced cells (p<0.01). TGF-β1-stimulated α-sma mRNA expression was attenuated by crude extra (from 0.125 mg/mL and F3 (25µg/mL) treatment, and protein-level α-sma inhibition was alsoapparent (p0.05). SB 431542 (25 µM) inhibited profileration, TGF-β1 (8 ng/mL-induced Smad3 activition via abrogation f CAGA-luc Smad reporter activity, and α-sma protein and mRNA expression in LX-2 cells (p<0.01). In conclusion, we demonstrated that Matrigel may be a usedful culture substrate to maintain LX-2 quiescence in in vitro studies, and studies, and S. sp. H6552 extract, F3, and SB 431542 exert anti-fibrotic activity toward human HSCs.